Determination of the kinetic parameters of Escherichia coli K12 (9481) in batch and continuous cultures - Ozbek, B; Lovitt, RW (KING FAHD UNIV PETROLEUM MINERALS, 1998)
The kinetic parameters of Escherichia coli K12 (9481) culture in a 21 (working volume) bioreactor was investigated both experimentally and theoretically during batch and continuous fermentations. This work reports the use of numerical optimization method for estimating the key Monod kinetic parameters, maximum specific growth rate, yield coefficient, saturation concentration of substrate and maintenance coefficient for Escherichia coli K12 (9481) in aerobic and anaerobic conditions, and in batch and continuous cultures. In defined medium, depending on the initial conditions, the calculated values of the kinetic parameters for both aerobic and anaerobic batch runs were: saturation concentration of glucose, 0.0137 g glucose/l and 0.0063 g glucose/l; maximum specific growth rate, 0.7811 h(-1) and 0.4992 h(-1); biomass yield, 0.4733 g cells/g glucose and 0.2625 g cells/g glucose and the maintenance coefficient for the cells, 0.0315 g glucose.(g cells)(-1).h(-1) and 0.3580 g glucose.(g cells)(-1).h(-1), respectively. Also, the calculated values of the kinetic parameters for both aerobic and anaerobic continuous runs were: saturation concentration of glucose, 0.0136 g glucose/l and 0.0053 g glucose/l; maximum growth rate, 0.8001 h(-1) and 0.4973 h(-1); biomass yield, 0.4904 g cells/g glucose and 0.2880 g cells/g glucose and the maintenance coefficient for the cells, 0.0441 g glucose.(g cells)(-1).h(-1) and 0.3758 g glucose.(g cells)(-1).h(-1), respectively.
Keywords: Escherichia coli K12 (9481); kinetic parameters; Science & Technology - Other Topics